TRANSFORMASI INTELEKTUAL ISLAM: INTEGRASI WARISAN KEILMUAN ABAD 13 DENGAN PENDIDIKAN ISLAM DI ERA DIGITAL - Muhammad Rizqi Fauzi; Sugeng Listyo Prabowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article examines the intellectual transformation of Islam, focusing on the 13th-century scientific legacy and the challenges facing Islamic education in today's digital age. The research method used is library research with a descriptive qualitative approach, which examines various literature related to the history of classical Islamic scholarship as well as the development of digital technology and its impact on Islamic education in the Digital Age. This study highlights how the 13th-century Islamic intellectual tradition, which integrated religious and scientific knowledge and developed the madrasah education system, has become a crucial foundation for facing the changing times. In the digital age, Islamic education faces various challenges such as disparities in technological access, low digital literacy among educators and students, and the risk of distortion of Islamic values ​​due to the dissemination of unfiltered digital content. However, the digital era also opens up significant opportunities through the use of e-learning platforms, artificial intelligence technology, project-based learning, and social media as a means of interaction and collaboration. The study concludes that the success of the transformation of Islamic education in the digital age depends heavily on the ability to balance the preservation of classical intellectual heritage with technological adaptation, thereby creating a generation of Muslims with integrated intellectual and spiritual intelligence and capable of facing global challenges. This research provides strategic recommendations for Islamic educational institutions to optimize digital technology effectively and ethically, in order to improve the quality of learning and the practice of Islamic values ​​amidst the dynamics of the times.